Associate Professor Ts. Dr. Mohd Azrul Hisham develops ErgoSmart Desk to alleviate back pain - Safriza, Baharuddin (UMPSA, 2024)
PEKAN, 3 July 2024 - Back pain, particularly Lower Back Pain (LBP), is a prevalent issue among individuals who spend extended hours in office environments, seated for up to seven or eight hours daily.